A comparative analysis of hedonic models of nutrition information and health claims on food products: An application to soup products. Issue 7 (3rd October 2018) - Giombi, Kristen C.; Muth, Mary K.; Levin, David
ABSTRACT: Over time, the quality of data on food purchases and label information has improved such that hedonic analyses to determine the implicit prices of product attributes can be conducted using more detailed data than in the past. With the availability of more extensive data, it is important to understand the characteristics of the data and implications of using different data sources on results of analyses. The purpose of this study was twofold: (1) compare results between two sources of label information and (2) develop a better understanding of the effects of product claims and nutrition information on the value of products to consumers. Trans fat claims, organic claims, private label, package size, and several nutrients were found to influence implicit prices for soup products, and the results between the two data sources are comparable.